Pewarisan Nilai-nilai Kearifan Lokal untuk Memproteksi Masyarakat Bali dari Dampak Negatif Globalisasi - Ni Putu Suwardani (Universitas Udayana, 2015)
This article analyses the importance of maintaining local wisdom for Balinese people in order to face various negative impacts of social changes brought about by globalisation. The symptom, which is basically felt by the Balinese today, is the fundamental socio-cultural change. The acceleration of the information coming along with the wave of globalization has been significantly experienced by the Balinese, both at the level of the “surface structure” (the attitudes and the pattern of behavior) and at the level of the “deep structure” (the value system, the life view, the philosophy, and the belief). The change is due to the culture contacts between countries in which there are dialectic fight between the contemporary values and those of the traditional where one tries to take the domination of another. Here, the hegemony and the neoliberal views are possibly coming and breaking all the aspects of life, including the values of the local culture ever obeyed firmly by the Balinese society. This condition leads to a spit and uncertain values situation because the people give more attention and respect to the modern values and marginalize the transcendental values. This is resulting in various violations of the moral values reflected by the feature, the style, and the life pattern of the society to occur. Therefore, reinforcement and inheritance of the Balinese local wisdom have to be conducted intensively to the Balinese younger generation.